Hubungan perilaku penggunaan media sosial dan tingkat pengetahuan gizi dengan kejadian anemia pada remaja putri - Nur Fauzun Ahsana; Ajib Jayadi; Radella Hervidea (THE JOURNAL OF Mother and Child Health Concerns, 2025)
Abstract Background: Anemia is a health problem worldwide, especially in developing countries where an estimated 30% of the world's population suffers from anemia. Anemia is common in society, especially in adolescents and pregnant women. Adolescents use gadgets/cellphones in various activities, one of which is social media which is currently trending among adolescents. Teenagers interacting too often with gadgets often make them late or even forget to eat, which can have an impact on their hemoglobin levels. Purpose: To determine the relationship between Social Media Usage Behavior and Nutrition Knowledge Level with the Incidence of Anemia in Adolescent Girls. Method: Quantitative research with a cross-sectional design, on June 14, 2022 in the classroom of SMP Negeri 1 Kotabumi, North Lampung. Respondents who participated in this study were 40 female students. The instruments used were questionnaires on social media usage behavior, knowledge, and hemoglobin (HB) level examinations. Results: Based on the results of the bivariate analysis study conducted with the Chi-square statistical test, the results obtained were p <0.05 (0.021) on social media usage behavior. While 0.006 (p <0.05) at the level of nutritional knowledge. Conclusion: There is a relationship between social media usage behavior and the incidence of anemia, and there is a relationship between the level of nutritional knowledge and the incidence of anemia. Suggestion: It is expected that schools can carry out activities of the School Health Unit (UKS), Youth Red Cross (PMR), and Youth Reproductive Health (KRR) to improve the health of students, especially adolescent girls, as well as Health Service Counseling for Adolescents. Keywords: Anemia; Adolescents; Hemoglobin Levels. Pendahuluan: Anemia merupakan salah satu masalah kesehatan di seluruh dunia terutama negara berkembang dimana diperkirakan 30% penduduk dunia menderita anemia. Anemia banyak terjadi di masyarakat terutama pada remaja dan ibu hamil. Para remaja menggunakan gadget/handphone dalam berbagai aktivitas salah satunya adalah media sosial yang sedang menjadi tren di kalangan remaja. Terlalu seringnya remaja berinteraksi dengan gadget membuat dirinya sering terlambat bahkan lupa makan yang dapat berdampak pada kadar hemoglobinnya. Tujuan: Untuk mengetahui hubungan Perilaku Penggunaan Media Sosial dan Tingkat Pengetahuan Gizi dengan Kejadian Anemia pada Remaja Putri. Metode: Penelitian kuantitatif dengan desain cross-sectional, pada tanggal 14 Juni 2022 di ruang kelas SMP Negeri 1 Kotabumi, Lampung Utara. Responden yang menjadi peserta dalam penelitian ini sebanyak 40 siswi. Instrumen yang digunakan berupa kuesioner perilaku penggunaan media sosial, pengetahuan, dan pemeriksaan kadar hemoglobin (HB). Hasil: Berdasarkan hasil penelitian analisis bivariat yang dilakukan dengan uji statistik Chi-square diperoleh hasil p < 0.05 (0.021) pada perilaku penggunaan media sosial. Sedangkan 0.006 (p < 0.05) pada tingkat pengetahuan gizi. Simpulan: Ada hubungan antara perilaku penggunaan media sosial dengan kejadian anemia, dan ada hubungan antara tingkat pengetahuan gizi dengan kejadian anemia. Saran: Diharapkan pihak sekolah dapat melaksanakan kegiatan Unit Kesehatan Sekolah (UKS), Palang Merah Remaja (PMR), dan Kesehatan Reproduksi Remaja (KRR) untuk meningkatkan kesehatan siswa khususnya remaja putri, serta Penyuluhan Pelayanan Kesehatan Bagi Remaja.  Kata Kunci: Anemia; Kadar Hemoglobin; Remaja.